The adoption of knowledge sharing culture in Malaysian banking sector UiTM Shah Alam / Norhafizah Semangin - Semangin, Norhafizah (2005)
Knowledge sharing culture has become a necessity in every organization in order to gain competitive advantage among competitors. In Malaysia, knowledge sharing culture has grown to be an important asset for companies to make decisions and solve critical problems. The banking sector is not excluded from this scenario. In order to have knowledge sharing culture environment, company must identified what are the factors that is needed to inculcate knowledge sharing among the people in the company. The employees and the management both play an important role to ensure the success of adopting knowledge sharing as a culture in the organization. Knowledge sharing may have already existed in the company but whether it has become a culture or not is yet to be known among them. Knowledge sharing can be implemented formally or informally. Chatting among colleagues is considered as informal knowledge sharing and written or printed documents stored in files are considered as formal knowledge sharing. Either way, knowledge sharing can still be adopted by many companies using appropriate medium and full support from the management such as providing the tools and technology for them to be able to share their knowledge. The current situation and pattern of knowledge sharing culture in Malaysia, especially in the banking sector will be identified. Problems that occurred in the process of knowledge sharing also will be tackled